A Systematic Review on Theses Works Carried out at the Post Graduate Department of Dravyaguna in Rajiv Gandhi Government Post Graduate Ayurvedic College and Hospital, Paprola, Himachal Pradesh from 2009 to 2021 - Pandit, Ram Deo; Upadhyaya, Ashwani; Gupta, Chandni; Rana, Kailash (International Research Journal of Ayurveda & Yoga, 2022)
Rajiv Gandhi Government Post Graduate Ayurvedic College and Hospital (RGGPGAC&H), Paprola (also known as Paprola Ayurvedic College) was established in 1972 as a private institution. It was taken over by the government of Himachal Pradesh in 1978, affiliating it to Himachal Pradesh University (HPU). Post Graduate Department of Dravyaguna (PGDD) at the college started in 2009; initially intake capacity of the department was two students per year which increased to three later. Since 2020 the intake capacity of PGDD is four students per year. Library and personal interview methods are used for this systematic review study. A total of 24 (5 experimental, 2 survey, 1 literary and 16 clinical) theses have been completed under the supervision of four faculties at the department. 8 theses studies are ongoing (3 clinical, 3 experimental, 1 survey and 1 literary). All those 24 theses studies occurred between 2009-2021 the yield significant results. The department has been continuously working hard on various research and developmental issues of Dravyaguna to promote and motivate Dravyaguna scholars all around.